Health Problems of the Geriatric People: A Community Based Study in a Rural Area in Bangladesh (TAJ: Journal of Teachers Association, 2009)
A community based cross-sectional study among the geriatric people i.e. 60 years and aboveage group was carried out in the rural villages of Rangpur district with a view to find out theircommon health problems and the relationship between the health problems and some of theirsocio-economical factors. A total of 1000 geriatric people were interviewed. Among them 73.6%were male and 26.4% were female, majority of them (47.8%) were in the age group 60-64 yearsand about 30% of them were smokers. About 86% of the respondents were suffering from eithera disease or diseases at the time of Interview. The most common diseases suffered by themwere arthritis, diarrhoea, hyperacidity and peptic ulcerative diseases, bronchitis, asthma,hypertension, cataract, dental caries, skin disease, diabetes mellitus, hydrocele, etc.A positive relationship of disease prevalence was found with educational status (p< .001),economical status (p